On the phenomenon of scientific work of Zbyszko Melosik - Śliwerski, Bogusław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Bogusław Śliwerski, On the phenomenon of scientific work of Zbyszko Melosik. Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 405–439. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.26.19 The subject of analyses are issues of research undertaken in scientific publications by Zbyszko Melosik from the Adam Mickiewicz University in Poznań, the content of which is of key significance to reforms in paedagogical sciences after the year 1989 in Poland, as well as to the understanding of international and domestic value of the cooperation of this scientist with academic circles. It is also an example of the establishment and evolution of the Poznań research school in culture, comparative and general paedagogy. They indicate a clear union between the conditions of sociocultural and education studies in light of the assumptions of post-modernism and critical paedagogy and the richness of sources by this author, connecting Polish paedagogical thought with the world discourse on socialisation and broadly understood education.